Microbiology of diverse acidic and non-acidic microhabitats within a sulfidic ore mine - Falteisek, Lukáš; Cepička, Ivan (Extremophiles, 2012)
A wide variety of microhabitats within the extremely acidic abandoned underground copper mine Zlaté Hory (Czech Republic) was investigated. SSU rDNA libraries were analyzed from 15 samples representing gossan, sulfide-leaching environments in the oxidation zone, and acidic water springs in the mine galleries. Microbial analyses were extended by analyses of chemical composition of water and solid phases and identification of arising secondary minerals. The microbial communities of the three main classes of microenvironments differed in almost every aspect. Among others, ecological partitioning of Acidithiobacillus ferrooxidans and the recently described A. ferrivorans was observed. Distinct types of communities inhabiting the water springs were detected. The more extreme springs (pH <3, conductivity >2 mS/cm) were inhabited by "Ferrovum" spp. and A. ferrivorans, whereas Gallionella sp. dominated the less extreme ones. A new role for gossan in the extremely acidic ecosystem is proposed. This zone was inhabited by a large diversity of neutrophilic heterotrophs that appeared to be continuously washed out to the acidic environments localized downstream. Five species originating in gossan were found in several acidic habitats. Here they can survive and probably serve as scavengers of dead biomass, particularly from chemoautotrophic growths. No such process has been described from acidic mine environments so far.
Keywords: Sulfides; geologické sedimenty; biodiverzita; sulfidy; Genes, rRNA; hornictví; Hydrogen-Ion Concentration; bakteriální geny; Mining; Minerals; Phylogeny; Bacteria; Czech Republic; Biodiversity; minerály; ekosystém; Česká republika; Geologic Sediments; Ecosystem; Genes, Bacterial; geny rRNA; fylogeneze; koncentrace vodíkových iontů; Gallionellaceae; Acidithiobacillus